Catalyst-free synthesis of 4-acyl-NH-1,2,3-triazoles by water-mediated cycloaddition reactions of enaminones and tosyl azide - Yang, Lu; Wu, Yuwei; Yang, Yiming; Wen, Chengping; Wan, Jie-Ping (Beilstein Journal of Organic Chemistry, 2018)
The synthesis of 4-acyl-NH-1,2,3-triazoles has been accomplished with high efficiency through the cycloaddition reactions between N,N-dimethylenaminones and tosyl azide. This method is featured with extraordinary sustainability by employing water as the sole medium, free of any catalyst or additive, authentically mild conditions (40 °C stirring) as well as practical scalability.
Keywords: additive-free; catalyst-free; cycloaddition; enaminones; on water; 1,2,3-triazole

(untitled) - Lipshutz, B. H.; Ghorai, S.; Cortes-Clerget, M. (Chem. – Eur. J., 2018)

(untitled) - Simon, M.-O.; Li, C.-J. (Chem. Soc. Rev., 2012)

(untitled) - Anastas, P.; Eghbali, N. (Chem. Soc. Rev., 2010)

(untitled) - Gawande, M. B.; Bonifácio, V. D. B.; Luque, R.; Branco, P. S.; Varma, R. S. (Chem. Soc. Rev., 2013)

(untitled) - Butler, R. N.; Goyne, A. G. (Chem. Rev., 2010)

(untitled) - Chanda, A.; Fokin, V. V. (Chem. Rev., 2009)

(untitled) - Guo, W.; Wu, B.; Zhou, X.; Chen, P.; Wang, X.; Zhou, Y.-G.; Liu, Y.; Li, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Li, Y.; Huang, Y.; Gui, Y.; Sun, J.; Li, J.; Zha, Z.; Wang, Z. (Org. Lett., 2017)

(untitled) - Zhang, F.-Z.; Tian, Y.; Li, G.-X.; Qu, J. (J. Org. Chem., 2015)

(untitled) - Álvarez, M.; Gava, R.; Rodríguez, M. R.; Rull, S. G.; Pérez, P. J. (ACS Catal., 2017)

(untitled) - Zhang, N.; Yang, D.; Wei, W.; Yuan, L.; Nie, F.; Tian, L.; Wang, H. (J. Org. Chem., 2015)

(untitled) - Xie, L.-Y.; Li, Y.-J.; Qu, J.; Duan, Y.; Hu, J.; Liu, K.-J.; Cao, Z.; He, W.-M. (Green Chem., 2017)

(untitled) - Xiao, F.; Chen, S.; Tian, J.; Huang, H.; Liu, Y.; Deng, G.-J. (Green Chem., 2016)

(untitled) - Liu, K.-J.; Fu, Y.-L.; Xie, L.-Y.; Wu, C.; He, W.-B.; Peng, S.; Wang, Z.; Bao, W.-H.; Cao, Z.; Xu, X.; He, W.-M. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Wu, C.; Xin, X.; Fu, Z.-M.; Xie, L.-Y.; Liu, K.-J.; Wang, Z.; Li, W.; Yuan, Z.-H.; He, W.-M. (Green Chem., 2017)

(untitled) - Li, W.; Yin, G.; Huang, L.; Xiao, Y.; Fu, Z.; Xin, X.; Liu, F.; Li, Z.; He, W. (Green Chem., 2016)

(untitled) - Tang, L.; Yang, Y.; Wen, L.; Yang, X.; Wang, Z. (Green Chem., 2016)

(untitled) - Lin, Y.-m.; Lu, G.-p.; Wang, G.-x.; Yi, W.-b. (J. Org. Chem., 2017)

(untitled) - Köhling, S.; Exner, M. P.; Nojoumi, S.; Schiller, J.; Budisa, N.; Rademann, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Chen, D.; Feng, Q.; Yang, Y.; Cai, X.-M.; Wang, F.; Huang, S. (Chem. Sci., 2017)

(untitled) - Yang, J.; Mei, F.; Fu, S.; Gu, Y. (Green Chem., 2018)

(untitled) - Liu, J.; Lei, M.; Hu, L. (Green Chem., 2012)

(untitled) - Reddy, G. T.; Kumar, G.; Reddy, N. C. G. (Adv. Synth. Catal., 2018)

(untitled) - Kolb, H. C.; Sharpless, K. B. (Drug Discovery Today, 2003)

(untitled) - Nandivada, H.; Jiang, X.; Lahann, J. (Adv. Mater., 2007)

(untitled) - Thirumurugan, P.; Matosiuk, D.; Jozwiak, K. (Chem. Rev., 2013)

(untitled) - Chen, Z.; Liu, Z.; Gao, G.; Li, H.; Ren, H. (Adv. Synth. Catal., 2017)

(untitled) - Xie, L.-Y.; Qu, J.; Peng, S.; Liu, K.-J.; Wang, Z.; Ding, M.-H.; Wang, Y.; Cao, Z.; He, W.-M. (Green Chem., 2018)

(untitled) - Huisgen, R. (Angew. Chem., Int. Ed. Engl., 1963)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Hein, J. E.; Fokin, V. V. (Chem. Soc. Rev., 2010)

(untitled) - Zhang, L.; Chen, X.; Xue, P.; Sun, H. H. Y.; Williams, I. D.; Sharpless, K. B.; Fokin, V. V.; Jia, G. (J. Am. Chem. Soc., 2005)

(untitled) - Destito, P.; Couceiro, J. R.; Faustino, H.; López, F.; Mascareñas, J. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Johansson, J. R.; Lincoln, P.; Nordén, B.; Kann, N. (J. Org. Chem., 2011)

(untitled) - Ramasastry, S. S. V. (Angew. Chem., Int. Ed., 2014)

(untitled) - Lima, C. G. S.; Ali, A.; van Berkel, S. S.; Westermann, B.; Paixão, M. W. (Chem. Commun., 2015)

(untitled) - Thomas, J.; Jana, S.; John, J.; Liekens, S.; Dehaen, W. (Chem. Commun., 2016)

(untitled) - Ramachary, D. B.; Shashank, A. B.; Karthik, S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Li, W.; Wang, J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Agard, N. J.; Preschner, J. A.; Bertozzi, C. R. (J. Am. Chem. Soc., 2004)

(untitled) - Ramachary, D. B.; Ramakumar, K.; Narayana, V. V. (Chem. – Eur. J., 2008)

(untitled) - Belkheira, M.; Abed, D. E.; Pons, J.-M.; Bressy, C. (Chem. – Eur. J., 2011)

(untitled) - Kwok, S. W.; Fotsing, J. R.; Fraser, R. J.; Rodionov, V. O.; Fokin, V. V. (Org. Lett., 2010)

(untitled) - Wan, J.-P.; Hu, D.; Liu, Y.; Sheng, S. (ChemCatChem, 2015)

(untitled) - Chen, Z.; Cao, G.; Song, J.; Ren, H. (Chin. J. Chem., 2017)

(untitled) - van Berkel, S. S.; Brauch, S.; Gabriel, L.; Henze, M.; Stark, S.; Vasilev, D.; Wessjohann, L. A.; Abbas, M.; Westermann, B. (Angew. Chem., Int. Ed., 2012)

(untitled) - Chen, Z.; Yan, Q.; Liu, Z.; Zhang, Y. (Chem. – Eur. J., 2014)

(untitled) - Cai, Z.-J.; Lu, X.-M.; Zi, Y.; Yang, C.; Shen, L.-J.; Li, J.; Wang, S.-Y.; Ji, S.-J. (Org. Lett., 2014)

(untitled) - Wan, J.-P.; Cao, S.; Liu, Y. (J. Org. Chem., 2015)

(untitled) - Bakulev, V. A.; Beryozkina, T.; Thomas, J.; Dehaen, W. (Eur. J. Org. Chem., 2018)
and references cited therein

(untitled) - Cheng, G.; Zeng, X.; Shen, J.; Wang, X.; Cui, X. (Angew. Chem., Int. Ed., 2013)

(untitled) - Wan, J.-P.; Cao, S.; Liu, Y. (Org. Lett., 2016)

(untitled) - Efimov, I.; Bakulev, V.; Beliaev, N.; Beryozkina, T.; Knippschild, U.; Leban, J.; Zhi-Jin, F.; Eltsov, O.; Slepukhin, P.; Ezhikova, M.; Dehaen, W. (Eur. J. Org. Chem., 2014)

(untitled) - Thomas, J.; Goyvaerts, V.; Liekens, S.; Dehaen, W. (Chem. – Eur. J., 2016)

(untitled) - Thomas, J.; Jana, S.; Liekens, S.; Dehaen, W. (Chem. Commun., 2016)

(untitled) - Cohrt, A. E.; Jensen, J. F.; Nielsen, T. E. (Org. Lett., 2010)

(untitled) - Hu, Q.; Liu, Y.; Deng, X.; Li, Y.; Chen, Y. (Adv. Synth. Catal., 2016)

(untitled) - Qvortrup, K.; Nielsen, T. E. (Chem. Commun., 2011)

(untitled) - Deng, X.; Lei, X.; Nie, G.; Jia, L.; Li, Y.; Chen, Y. (J. Org. Chem., 2017)

(untitled) - Bakulev, V. A.; Beryozkina, T. A. (Chem. Heterocycl. Compd., 2016)